2019
DOI: 10.1186/s13071-018-3194-9
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity of Ehrlichia canis associated with high co-infection rates in Rhipicephalus sanguineus (s.l.)

Abstract: BackgroundRhipicephalus sanguineus sensu lato (s.l.) is the most widely distributed ixodid tick and is a vector of major canine and human pathogens. High-throughput technologies have revealed that individual ticks carry a high diversity of pathogens, including bacteria, protozoa and viruses. Currently, it is accepted that co-infections (multiple pathogen species within an individual) are very common in ticks and influence pathogen acquisition and transmission as well as host infection risk. However, little is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…On the other hand, the allotype 3, considered a T-helper cell epitope, revealed an “excess” of nonsynonymous substitutions in the great majority of the samples. The low Sal-1 allotype 3 frequency has already been reported in China [ 63 ], Mexico [ 69 ], Sudan [ 61 ], and also in Brazil [ 27 , 28 , 71 ]. Thus, it is reasonable to speculate that such nonsynonymous polymorphisms are not essential for P .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the allotype 3, considered a T-helper cell epitope, revealed an “excess” of nonsynonymous substitutions in the great majority of the samples. The low Sal-1 allotype 3 frequency has already been reported in China [ 63 ], Mexico [ 69 ], Sudan [ 61 ], and also in Brazil [ 27 , 28 , 71 ]. Thus, it is reasonable to speculate that such nonsynonymous polymorphisms are not essential for P .…”
Section: Discussionmentioning
confidence: 93%
“…A large number of VK210’s substitutions and length polymorphisms have been found worldwide [ 26 , 69 ]. However, its nonapeptide repeat structure remained conserved, probably by intragenic shuffling, as previously suggested for P .…”
Section: Discussionmentioning
confidence: 99%
“…4). Although studies from Pakistan have reported ehrlichiosis in dogs using blood smear examination [58] and molecular tools [38, 59], no information is available on the epidemiology of ehrlichiosis in bovines from Pakistan. Recently, one study investigated TBPs in bovine ticks from Punjab, Pakistan, and reported a high prevalence of Ehrlichia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Dermacentor is of public and veterinary health concern as a vector reservoir for several pathogens with unknown potential risks in Pakistan. R. sanguineus , a vector of microorganisms of medical and veterinary health concern such as Hepatozoon canis and Ehrlichia canis (Dantas-Torres et al, 2018; Cabezas-Cruz et al, 2019) was collected for the first time from wild boars in the region.…”
Section: Discussionmentioning
confidence: 99%